Long term changes of the throwing arm of former elite javelin throwers - Schmitt, H.; Hansmann, H. M.; Brocai, R. C.; Loew, M. (International Journal of Sports Medicine, 2001)
The aim of this study was to determine long term changes in shoulder and elbow joints of former elite javelin throwers. Twenty-one elite javelin throwers were examined at an average of 19 years after the end of their high performance phase. Mean age at examination was 50 years. Functional assessment of both shoulders was determined by the Constant-score. The shoulder of the throwing arm was examined by magnetic resonance imaging. Both elbow joints were examined clinically and radiographically. Five athletes complained about transient shoulder pain in their throwing arm affecting activities of daily living, fourteen athletes had a deficit of internal rotation of at least ten degrees. Constant-scores of throwing arms were six points lower than those of non-throwing arms (P < 0.05). Complete ruptures and partial tears of the rotator cuff were frequent. Three athletes complained about transient elbow pain in their throwing arm affecting activities of daily living; ten athletes had a deficit of extension of more than five degrees. All dominant elbows had advanced arthrotic alterations (osteophytes, sclerosis) compared to the non-dominant side. Athletes who trained with weights of more than 3 kg had a significantly higher risk of degenerative changes than athletes who did not (P < 0.01). We therefore recommend to avoid throwing training with weights of more than 3kg.